2009
DOI: 10.1016/j.archger.2008.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A 10-year follow-up study on subjective well-being and relationships to person–environment (P–E) fit and activity of daily living (ADL) dependence of older Swedish adults

Abstract: In order to investigate how well-being and ill health is affected by the process of aging, the main aim was to investigate these self-perceived aspects of health over a 10-year period among older Swedish adults. The aim was also to study how these aspects correlated with objectively assessed functional limitations, use of mobility device, person-environment (P-E) fit; (also denoted accessibility) problems in housing, and activity of daily living (ADL) dependence. Using the Swedish national population register,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 24 publications
2
21
0
Order By: Relevance
“…On the cross-sectional level, largely confirming previous research (Oswald et al 2007a, b;Werngren-Elgström et al 2009), we found as hypothesised that MAP was consistently related with ADL independence/dependence as well as life satisfaction, positive affect, and depression. Larger MAP was linked with more unpleasant outcomes and the relative contribution of MAP to the explanation of outcome variation was highest, as predicted, with respect to ADL independence/dependence.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…On the cross-sectional level, largely confirming previous research (Oswald et al 2007a, b;Werngren-Elgström et al 2009), we found as hypothesised that MAP was consistently related with ADL independence/dependence as well as life satisfaction, positive affect, and depression. Larger MAP was linked with more unpleasant outcomes and the relative contribution of MAP to the explanation of outcome variation was highest, as predicted, with respect to ADL independence/dependence.…”
Section: Discussionsupporting
confidence: 91%
“…Guralnik et al 2000), this relation should become even stronger, if reduced functional limitations are considered in conjunction with unfavourable physical environmental circumstances. MAP may also reveal linkages with well-being related outcomes (Werngren-Elgström et al 2009), because low accessibility may come with lowered attainment of desired life goals (such as staying put as long as possible) and thus impact on life satisfaction, affect, and depression. Generally, however, we expect that the relationship of MAP with performance in activities of daily living should be more substantial as compared with well-being related outcomes, because the latter causal linkage is probably more indirect and unspecific.…”
Section: Introductionmentioning
confidence: 98%
“…Another key finding was that the residents in both RCFs spent most of their time alone in their apartments. Several studies highlight the importance of supportive environments that meet the needs of older people with high levels of frail health (24,25,46). Lawton and Nahemow's ecological model on ageing (23) argues that dependence on an environment increases with frailty.…”
Section: Discussionmentioning
confidence: 99%
“…According to some researchers (24), the relationship between a persons' functioning and the demands of his or her physical environment can be described in terms of accessibility. With increasing levels of frail health, an accessible physical environment becomes more important (25) and must be adjusted to support the persons' needs (23). Today, there are demands that decisions about the design of the healthcare architecture should be based on the best available information from credible research and evaluations of existing building projects.…”
Section: Introductionmentioning
confidence: 99%
“…A major European initiative found that in-home person-environment fit 3 enhances autonomy among older people. 4 While rehabilitation professionals generally acknowledge the importance of home accessibility, little, if any, empirical evidence links the presence of home environmental barriers to NH use.…”
mentioning
confidence: 99%